Penggunaan Media Gambar untuk Meningkatkan Keterampilan Menulis Deskripsi Peserta Didik Kelas 3 SDN Prajurit Kulon - Marina Dini Ari Pratiwi; Sahrul Farosy; Nuvitaliya Rahmawati; Dominggas Galanggoga; Rani Jayanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
Writing descriptive texts is one of the essential language skills that elementary school students need to master. However, many third-grade students at SDN Prajurit Kulon still face difficulties in producing descriptive writing due to the lack of engaging learning media. This study aims to improve students’ descriptive writing skills through the use of picture media. The research was conducted in one meeting using a qualitative descriptive approach. The subjects were 22 third-grade students of SDN Prajurit Kulon. Data were collected through classroom observation and students’ group work. Students were divided into small groups to observe the provided pictures and collaboratively transform their observations into descriptive texts. The findings reveal that the use of picture media in group writing activities encouraged students to be more active, creative, and motivated in developing ideas into descriptive writing. The implication of this study suggests that picture media can serve as an effective alternative learning tool to enhance descriptive writing skills in elementary schools.